Hydrothermal Synthesis and Properties of Yb3+/Tm3+ Doped Sr2LaF7 Upconversion Nanoparticles - Milićević, Bojana; Periša, Jovana; Ristić, Zoran; Milenković, Katarina; Antić, Željka; Smits, Krisjanis; Kemere, Meldra; Vitols, Kaspars; Sarakovskis, Anatolijs; Dramićanin, Miroslav D. (MDPI, 2023)
We report the procedure for hydrothermal synthesis of ultrasmall Yb3+/Tm3+ co-doped Sr2LaF7 (SLF) upconversion phosphors. These phosphors were synthesized by varying the concentrations of Yb3+ (x = 10, 15, 20, and 25 mol%) and Tm3+ (y = 0.75, 1, 2, and 3 mol%) with the aim to analyze their emissions in the near IR spectral range. According to the detailed structural analysis, Yb3+ and Tm3+ occupy the La3+ sites in the SLF host. The addition of Yb3+/Tm3+ ions has a huge impact on the lattice constant, particle size, and PL emission properties of the synthesized SLF nanophosphor. The results show that the optimal dopant concentrations for upconversion luminescence of Yb3+/Tm3+ co-doped SLF are 20 mol% Yb3+ and 1 mol% Tm3+ with EDTA as the chelating agent. Under 980 nm light excitation, a strong upconversion emission of Tm3+ ions around 800 nm was achieved. In addition, the experimental photoluminescence lifetime of Tm3+ emission in the SLF host is reported. This study discovered that efficient near IR emission from ultrasmall Yb3+/Tm3+ co-doped SLF phosphors may have potential applications in the fields of fluorescent labels in bioimaging and security applications. © 2022 by the authors. --//-- Milićević B., Periša J., Ristić Z., Milenković K., Antić Ž., Smits K., Kemere M., Vitols K., Sarakovskis A., Dramićanin M.D., Hydrothermal Synthesis and Properties of Yb3+/Tm3+ Doped Sr2LaF7 Upconversion Nanoparticles, (2023) Nanomaterials, 13 (1), art. no. 30, DOI: 10.3390/nano13010030, https://www.scopus.com/inward/record.uri?eid=2-s2.0-85145824982&doi=10.3390%2fnano13010030&partnerID=40&md5=aaad8d348b12b86447784dd82261d5f7, published under the CC BY 4.0 license.
The authors from Serbia acknowledge funding from the Ministry of Science, Technological Development and Innovation of the Republic of Serbia. The authors from Latvia acknowledge funding from the European Union’s Horizon 2020 Framework Programme H2020-WIDESPREAD-01-2016-2017-TeamingPhase2 under grant agreement No. 739508, project CAMART2.
Keywords: Research Subject Categories::NATURAL SCIENCES; fluoride; morphology; nanophosphor; NIR emission; Tm3+ emission; upconversion